EFFECTS OF JUDICIAL TRANSFORMATION FRAMEWORK (2012-2016) ON THE PERFORMANCE OF THE JUDICIARY IN KENYA - BOSIRE, ERIC MOKWARO; KIVOI, DOUGLAS; NDUVI, STEVE (Archives of Business Research, 2018)
The purpose of this study was to examine whether the transformation of the judiciary (using Business Process Reengineering as a proxy) improved the performance of Judiciary in Kenya. A review of the literature showed that there is scanty information on how the Public Sector could improve on service delivery by implementing BPR, especially in developing economies. The study targeted a population of 320, drawn from Judicial Officers, Judicial Staff, and advocates in stations within Nairobi and Kiambu Counties. Quota sampling method was used to sample the population. Data was collected through structured questionnaires. Descriptive statistics was used to define the study variables particularly the sample profile. Pearson correlation coefficient was used to determine the level of significance of related variables, Chi-Square test to ascertain the existence of a significant association between variables and Regression analysis to determine the predictive power of BPR on the performance of the Judiciary. The results of the study showed a significant effect of the implementation of BPR on the performance of the Judiciary. In conclusion, the successful implementation of BPR was found to be premised on the recruitment of visionary top leadership, and change of organizational focus. To that extent, the need to have an organizational wide commitment is inevitable.